Research Progress on N-Heterocyclic Carbene Catalyzed Reactions for Synthesizing Ketones through Radical Mechanism - Wan, Dan-Hong; Yang, Hai-Bin (Synthesis, 2022)
NHC-catalyzed radical cross-coupling reactions have been recently developed; they provide an efficient method to access ketones from aldehydes or carboxylic acid derivatives with sp3-hybridized carbon radical precursors. This reaction has indirectly solved the limitations in the scope of coupling partners in NHC umpolung catalyzed reactions of aldehydes. In this short review, we present some recent advances in NHC-catalyzed radical reactions, with a focus on the construction of the C–C(CO) bond.1 Introduction2 Oxidative Generation of NHC-Derived Ketyl Radical2.1 NHPI Redox-Active Esters2.2 Katritzky Pyridinium Salts2.3 Alkyl Halides2.4 Aryl Halides2.5 Compounds Containing N–O Bond2.6 Diazo Esters2.7 Others3 Reductive Generation of NHC-Derived Ketyl Radical3.1 Hantzsch Esters3.2 Sulfinates3.3 Electron-Rich Arenes3.4 Amines3.5 Organoborane Reagents4 Conclusion
Keywords: N-heterocyclic carbene; catalysis; radical; ketone; C–C(CO) bond; coupling